Three orphan nuclear receptors in the scleractinian coral Pocillopora damicornis from the Pacific coast of Costa Rica - Tarrant, Ann M. (2008)
Within the animal kingdom, nuclear receptors modulate transcription to regulate diverse processes including embryonic development, energetic homeostasis and sexual differentiation. To date, nuclear receptor sequences have been reported in only a few cnidarian species, and little is known about nuclear receptor function in cnidarians. We have identified three nuclear receptor genes expressed in Pocillopora damicornis coral colonies (PdNR1, PdNR6, and PdNR7). The cDNA and deduced amino acid sequences indicate that these three genes are closely related to nuclear receptors previously reported in Acropora millepora planula larvae (AmNR1, AmNR6, and AmNR7). None of the three P. damicornis nuclear receptors are apparent homologs of known ligand-activated receptors. Two are most closely related to vertebrate genes important in neural differentiation and signaling (subfamily 2E, tailless genes and subfamily 2F, COUP-TFs). The third cannot be unambiguously classified within a currently recognized subfamily. Future studies are needed to describe the roles of nuclear receptors in cnidarian development and physiology. Rev. Biol. Trop. 56 (Suppl. 4): 39-48. Epub 2009 June 30.